Олеогранулема полового члена у подростка (клиническое наблюдение) - Т. Kh. Nazarov (Andrologiâ i Genitalʹnaâ Hirurgiâ, 2021)
The authors present a clinical observation of oleogranuloma of the penis in an adolescent. The analysis of domestic and foreign literature demonstrates the absence of this nosology in adolescence. The relevance of oleogranuloma of the penis and modern tactics of surgical treatment are highlighted.